Phase Transfer Catalysis Assisted Thorpe Reaction for the Synthesis of 3-Aminothiophene-2-carboxylates - R. D. Shah (E-Journal of Chemistry)
Thorpe cyclization constructing synthetically important methyl or ethyl 3-amino-4-arylthiophene-2-carboxylates has been studied using eco friendly phase transfer catalysis technique. 3-Amino-4-arylthiophene-2-carboxylates have been synthesized from 3-hydroxy-2-arylacrylonitriles and thioglycolates under different solid-liquid phase-transfer conditions.